Criminal Sanctions against Taxpayer Who are Negligent to Register Land and Building Taxes - Made Putri Pradnya Parahita; Simon Nahak; I Ketut Widia (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
One of the most common problems related to land and building tax is where there are citizens who are aware of their obligation to pay taxes by registering their objects, but due to certain circumstances, the taxpayer does not register the tax object he owns. This study aims to find out the regulation of criminal sanctions against taxpayers who do not register land and building tax and to find out the criminal liability of taxpayers who do not register the object of land and building tax. This study uses normative research that starts with an indication of the obscurity of legal norms. The results of this study showed that the provision of sanctions is needed as a form of the last effort to realize the certainty of tax activities going well. Sanctions given can be in the form of administrative sanctions in the form of fines to criminal sanctions in the form of prison or confinement, which can be imposed on taxpayers and related officials. Criminal liability in the field of taxation arises when each taxpayer is indicated to have committed a tax crime. The intended taxpayer is an individual taxpayer or legal entity or corporation. Likewise, it has been regulated that starting from the taxpayer, tax officials/employees, to third parties have their respective criminal liabilities. The legal basis is Law Number 28 of 2007 concerning General Provisions and Tax Procedures. The advice given is the need for strict rules regarding criminal sanctions against land and building tax registration.